2020
DOI: 10.1017/s1092852920001145
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic stress disorder in train crash survivors in Italy: the role of mood spectrum dysregulations and intrusiveness

Abstract: Background. To explore relationships among post-traumatic stress disorder (PTSD), depressive spectrum symptoms, and intrusiveness in subjects who survived the crash of a train derailed carrying liquefied petroleum gas and exploded causing a fire. Methods. A sample of 111 subjects was enrolled in Viareggio, Italy. AMOS version 21 (IBM Corp, 2012) was utilized for a structural equation model-path analysis to model the direct and indirect links between the exposure to the traumatic event, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Several factors directed the choice to use the IES-R to evaluate the convergent validity of the COVID-19-PTSD. First of all, although the IES-R has not been validated in the general Italian population, it was used to assess the PTSD symptomatology in many Italian samples [18][19][20][21][22][23][24]29,30]), which confirmed its adequate reliability. Moreover, both a validation of the previous version (IES) [31] and a published translation of the current version (IES-R) [26] led us to consider the IES-R as an appropriate tool to use for assessing the convergent validity of the COVID-19-PTSD questionnaire.…”
Section: Impact Of Event Scale-revised (Ies-r)mentioning
confidence: 99%
“…Several factors directed the choice to use the IES-R to evaluate the convergent validity of the COVID-19-PTSD. First of all, although the IES-R has not been validated in the general Italian population, it was used to assess the PTSD symptomatology in many Italian samples [18][19][20][21][22][23][24]29,30]), which confirmed its adequate reliability. Moreover, both a validation of the previous version (IES) [31] and a published translation of the current version (IES-R) [26] led us to consider the IES-R as an appropriate tool to use for assessing the convergent validity of the COVID-19-PTSD questionnaire.…”
Section: Impact Of Event Scale-revised (Ies-r)mentioning
confidence: 99%
“…Depression was almost significantly associated with PTSD between 10 days and 2.5 years after the trauma (Bedaso et al, 2020; Blanchard et al, 1995a, 1995b; da Conceição Lemos, 2013; Hodgson and Webster, 2011; Irish et al, 2008; Khodadadi-Hassankiadeh et al, 2017b; Miniati et al, 2021; Ning et al, 2017; Ryb et al, 2009; van den Heuvel et al, 2016; Wang et al, 2005; Yohannes et al, 2018). Although most studies reported it as a pretrauma factor, studies by Khodadadi-Hassankiadeh et al (2017a) and Hodgson and Webster (2011) demonstrated depression as a post-traumatic predictor between 1 and 6 months.…”
Section: Resultsmentioning
confidence: 99%
“…11 However, not everyone who suffers stress develops psychological or mental illnesses. 12 Staff coping use various strategies such as social and personal resources, as well as social support, optimism, and resilience, operate as protective factors. 13,14 Resilience is described as an individual's ability to manage great hardship and recover rapidly, and it has been associated with a lower risk of mental illness.…”
Section: Introductionmentioning
confidence: 99%